2017
DOI: 10.1038/ncomms14043
|View full text |Cite
|
Sign up to set email alerts
|

A ligand-directed divergent catalytic approach to establish structural and functional scaffold diversity

Abstract: The selective transformation of different starting materials by different metal catalysts under individually optimized reaction conditions to structurally different intermediates and products is a powerful approach to generate diverse molecular scaffolds. In a more unified albeit synthetically challenging strategy, common starting materials would be exposed to a common metal catalysis, leading to a common intermediate and giving rise to different scaffolds by tuning the reactivity of the metal catalyst through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 68 publications
(70 reference statements)
0
38
0
2
Order By: Relevance
“…We had observed that treating crotyl ether enyne substrate 6a ( E/Z = 3:1) with 5 mol‐% of a cationic gold(I) catalyst with different ligands could selectively provide spirooxindole 9a and quinolone 10a in good yields (Table , entries 1–3) . The cycloisomerization cascade catalyzed by NHC–gold(I) catalyst ( I ) delivered a spirooxindole 9a as the major product in 43 % yield along with quinolone 10a in 7 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…We had observed that treating crotyl ether enyne substrate 6a ( E/Z = 3:1) with 5 mol‐% of a cationic gold(I) catalyst with different ligands could selectively provide spirooxindole 9a and quinolone 10a in good yields (Table , entries 1–3) . The cycloisomerization cascade catalyzed by NHC–gold(I) catalyst ( I ) delivered a spirooxindole 9a as the major product in 43 % yield along with quinolone 10a in 7 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…Quinolone 229 was discovered as potent autophagy inhibitor (IC 50 =4.8 μM), and the df‐ oxindoles 230 and 231 were identified as Hedgehog inhibitor (IC 50 =3.31 and 2.75 μM). Moreover, further investigation on the most potent hedgehog inhibitor i. e. df‐ oxindole 231 revealed that it inhibited the transmembrane protein SMO trafficking to cilia …”
Section: Divergent Enyne Cycloisomerization Reactions In Scaffold DIVmentioning
confidence: 99%
“…Moreover, further investigation on the most potent inhibitor i.e. df‐ oxindole 42 b revealed that it inhibited trafficking of the transmembrane protein SMO to cilia …”
Section: Nature Inspired Chemotypes: Roadmap To Unique Chemical Spacementioning
confidence: 99%
“…However, unlike total synthesis of natural products or multistep synthesis of natural product analogues, often short and efficient synthesis designs delivering more than one scaffolds are required for library construction. For instance, Stockman et al designed a two-directional strategy using a symmetrical "rope-like" ketodienolate (23, Figure 4), which followed a number of separate tandem reactions to build many diverse and natural product-like scaffolds (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The scaffolds were thus built up in a quick and elegant manner and were already equipped with functional groups for further elaboration.…”
Section: Nature Inspired Chemotypes: Roadmap To Unique Chemical Spacementioning
confidence: 99%
See 1 more Smart Citation